The Australian monsoon, Part 2 : Depressions and cyclones (MAUSAM, 2001)
A study of the NCEP/NCAR Reanalysis for the Australian region during the southern summer reveals that most of the depressions and cyclones over the region form and develop in a stationary wave that develops along the continent's northern coastline during this period due to land-sea thermal contrast. The structure and properties of the stationary wave are brought out in detail and internal and external forcings that lead to its development into depressions and cyclones are discussed. Environmental factors that appear to influence the movement and recurvature of cyclones over the region are discussed with two case studies.